A cost/benefit analysis of Irish airlines - O'Donoghue, M. (Statistical and Social Inquiry Society of Ireland, 1969)
This paper deals with an attempt to measure the economic contribution which the Irish airlines (Aer Lingus and Aer Linte) make to the economy, and is based on a report prepared for the company in 1968
Read before the Society, 16 May 1969
Keywords: Cost benefit analysis; Irish airlines; Transport; Irish aviation industry; 314.15